2019
DOI: 10.1101/640177
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Varied effects of algal symbionts on transcription factor NF-κB in a sea anemone and a coral: possible roles in symbiosis and thermotolerance

Abstract: Many cnidarians, including the reef-building corals, undergo symbiotic mutualisms with photosynthetic dinoflagellate algae of the family Symbiodiniaceae. These partnerships are sensitive to temperature extremes, which cause symbiont loss and increased coral mortality.Previous studies have implicated host immunity and specifically immunity transcription factor NF-κB as having a role in the maintenance of the cnidarian-algal symbiosis. Here we have further investigated a possible role for NF-κB in establishment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 72 publications
0
11
2
Order By: Relevance
“…This demonstrates for the first time that symbiont phagocytosis massively suppresses transcription of immunity-related genes in the host at the cellular level. Moreover, in contrast to all previous organismal-wide analyses, we did not find the NF-κB transcription factor itself to be downregulated in symbiotic cells (Mansfield et al, 2019;Wolfowicz et al, 2016;Mansfield et al, 2017) suggesting that its own transcriptional regulation is not required for symbiosis establishment.…”
Section: Symbiosis Establishment Broadly Suppresses Host Cell Immunitcontrasting
confidence: 99%
See 1 more Smart Citation
“…This demonstrates for the first time that symbiont phagocytosis massively suppresses transcription of immunity-related genes in the host at the cellular level. Moreover, in contrast to all previous organismal-wide analyses, we did not find the NF-κB transcription factor itself to be downregulated in symbiotic cells (Mansfield et al, 2019;Wolfowicz et al, 2016;Mansfield et al, 2017) suggesting that its own transcriptional regulation is not required for symbiosis establishment.…”
Section: Symbiosis Establishment Broadly Suppresses Host Cell Immunitcontrasting
confidence: 99%
“…Previous transcriptomic analyses comparing aposymbiotic to symbiotic Aiptasia larvae and adult animals revealed several immune-related genes to be downregulated in response to symbiosis (reviewed in Mansfield and Gilmore, 2018). Specifically, symbionts have been proposed to induce immune suppression through NF-κB downregulation, possibly via TGFbsignalling (Berthelier et al, 2017;Detournay et al, 2012;Mansfield et al, 2019Mansfield et al, , 2017. In contrast, heterologous microalgae are thought to activate host innate immunity leading to their subsequent removal (Mansfield et al, 2019;reviewed in Mansfield and Gilmore, 2018;Mohamed et al, 2018).…”
Section: Symbiosis Establishment Broadly Suppresses Host Cell Immunitmentioning
confidence: 99%
“…Aiptasia is a tropical anemone that has been used as a model for cnidarian symbiosis with algal dinoflagellates in the family Symbiodiniaceae (55). Colonization of both larval and adult Aiptasia anemones with algal symbionts of certain strains results in the downregulation of NF-B transcripts, protein, and DNA-binding activity (23,56,57). Conversely, induction of loss of symbiosis with either chemical or heat treatment results in increased levels of NF-B expression and activity (23), and Aiptasia anemones lacking symbionts are more resistant to bacterial infection than ones with symbionts (57).…”
Section: Basal Nf-bs Likely Have Roles In Development and Immunitymentioning
confidence: 99%
“…Characterization of this protein is largely limited to variants associated with immune reactions in humans (e.g., Nussenblatt et al, 1982). Given the importance of host immune activation during the establishment and maintenance of symbiosis in corals (Mansfield et al, 2019) and the fact that these species have been found to host subtly different symbiont populations (Green et al, 2014), this differentially regulated transcript with antigenic potential deserves further investigation for its potential role in host-symbiont recognition.…”
Section: Transcriptomic Differences Between Orbicella Speciesmentioning
confidence: 99%